Numerical study on the dynamics and mass transfer characteristics of a radial offset jet. Issue 3 (2014) - ,; ,; ,; ,; ,
Abstract : Purpose – A radial offset jet has the flow characteristics of a radial jet and an offset jet, which are encountered in many engineering applications. The purpose of this paper is to study the dynamics and mass transfer characteristics of the radial offset jet with an offset ratio 6, 8 and 12.Design/methodology/approach – Three turbulence models, namely the SST k‐? model, detached eddy simulation model, and improved delayed detached eddy simulation (IDDES), were applied to the radial offset jet with an offset ratio eight and their results were compared with experimental results. The contrasting results, such as the distributions of mean and turbulent velocity and pressure, show that the IDDES model was the best model in simulating the radial offset jet. The results of the IDDES were analyzed, including the Reynolds stress, turbulent kinetic energy, triple‐velocity correlations, vertical structure and the tracer concentration distribution.Findings – In the axisymmetric plane, Reynolds stresses increase to reach a maximum at the location where the jet central line starts to be bent rapidly, and then decrease with increasing distance in the radial direction. The shear layer vortices, which arise from the Kelvin‐Helmholtz instability near the jet exit, become larger scale results in the entrainment and vortex pairing, and breakdown when the jet approaches the wall. Near the wall, the vortex swirling direction is different at both front and back of attachment point. In the wall‐jet region, the concentration distributions present self‐similarity while it keeps constant below the jet in the recirculation region.Research limitations/implications – The radial offset jet with other offset ratio and exit angle is not considered in this paper and should be investigated.Originality/value – The results obtained in this paper will provide guidance for studying similar flow and a better understanding of the radial offset jet. Acknowledgements : Funding was provided by the National Natural Science Foundation of China (Nos 11172218, 10972163, 51079102), Academic Leaders Program of Wuhan City (No. 201150530140), and Academic award for excellent PhD candidates funded by Ministry of Education of China.